LINE MANAGERS' AND SUBORDINATES' PERCEPTIONS OF INDIVIDUAL DEVELOPMENT Case Nokia ERP Development Competence Center - Jyllilä, Katjalina (My University, 2008)
This aim of this research was to examine line managers’ and subordinates’ perceptions of individual development in the case organization, Nokia Enterprise Resource Planning unit. The research questions concerned the overall importance of individual development, the ownership of development actions, motivation for development, and the importance of different development methods and tools. Theoretical review introduces several human resource management models, all of which have development as an essential part. Furthermore, theoretical frame gives some views to the subject of human resource development, and its’ relation to individual development. Finally, line manager involvement in human resource management and development is discussed. The on-line survey was carried out in unit in spring 2007. The data were analysed with SPSS. Frequencies were studied from line manager and subordinate groups and independent samples T-test was used to compare the answers of both groups. The research results showed that line managers’ and subordinates’ perceptions concerning the subject were consistent in overall importance of development, and in the importance of development tools and methods. Both line managers and subordinates felt that the ownership of individual development lies primarily within subordinate, but line managers also have the responsibility to support the overall process. Furthermore, subordinates felt that the upper management has or should take more responsibility for individual development. There were significant differences in the motivational factors for development. Subordinates felt that preparing for future needs was an important motivational factor, whereas line managers felt that commitment to organization was more important. These findings help line managers and subordinates understand each others’ views better. Furthermore, this research will help in planning development related training and communication.
Keywords: individual development; HRD; HRM; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|